Nuevos registros de hepáticas (Marchantiophyta) para la Región de Los Ríos, Chile - CUVERTINO-SANTONI, JORGE; OSORIO-ZÚÑIGA, FELIPE; CHAURA, RODRIGO (Gayana Botánica, 2015)
Fifteen new regional and one new provincial record are reported for Los Ríos Region, Chile. Notes on the geographical distribution and specimen data are provided for each taxon.